GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG PENCEGAHAN PENYAKIT PASCA BANJIR DI DESA DATAHU KECAMATAN TIBAWA - Vegita D. Imran; Pipin Yunus; Haslinda Damansyah (Jurnal Rumpun Ilmu Kesehatan, 2023)
A disaster is an event caused by nature and humans. Disaster can result in victims of human suffering, loss of property, environmental damage, damage to facilities and, infrastructure, public facilities, and disruption of the life and livelihood of the community. The purpose of research was to determine the knowledge and attitudes of the community about the prevention of post-flood disease in Datahu village, Tibawa sub-district. This research method uses the descriptive quantitative method. The sample of this research is 76 people using an accidental sampling technique. The results of this study indicate that public knowledge of 76 respondents there are 65 respondents with good knowledge and 11 respondents with less knowledge and public attitudes. Of 76 respondents there are 70 respondents have good attitudes, and 6 have poor attitudes. The research concluded that the description of the level of knowledge and attitudes of the community about post-flood disease prevention in Datahu village, Tibawa sub-district was in the excellent category.